2020
DOI: 10.5327/z2176-947820200533
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento De Citronela (Cymbopogon Winterianus) Irrigada Com Esgoto Doméstico Tratado E Com Água De Abastecimento

Abstract: Este trabalho teve como objetivo avaliar o desenvolvimento de capim citronela (Cymbopogon winterianus) irrigado com água de abastecimento fornecida pela concessionária (TA), esgoto doméstico tratado, após a adição de cloro (TB), e esgoto doméstico tratado, antes da adição de cloro (TC). Utilizou-se o efluente de uma estação de tratamento de esgoto (ETE) do tipo reator anaeróbio de fluxo ascendente (RAFA). A irrigação, com cada efluente, foi realizada em sete vasos, cada vaso com duas mudas do vegetal, totaliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…[2], investigating the influence of different doses of wastewater, associated with mineral fertilization, on plant growth and production in maize cultivation, found that the application of wastewater did not reduce plant yield. [3] evaluated the development of lemon grass (Cymbopogon winterianus) irrigated with treated domestic sewage, from an Upflow Anaerobic Sludge Blanket (UASB) treatment plant, and verified a higher potential for the use of nutrients when compared to that irrigated with domestic supply water. [4] investigated the growth of sunflower plants irrigated with tap water and treated domestic sewage effluent associated with organic fertilization, in the Brazilian semi-arid region.…”
Section: Introductionmentioning
confidence: 99%
“…[2], investigating the influence of different doses of wastewater, associated with mineral fertilization, on plant growth and production in maize cultivation, found that the application of wastewater did not reduce plant yield. [3] evaluated the development of lemon grass (Cymbopogon winterianus) irrigated with treated domestic sewage, from an Upflow Anaerobic Sludge Blanket (UASB) treatment plant, and verified a higher potential for the use of nutrients when compared to that irrigated with domestic supply water. [4] investigated the growth of sunflower plants irrigated with tap water and treated domestic sewage effluent associated with organic fertilization, in the Brazilian semi-arid region.…”
Section: Introductionmentioning
confidence: 99%